Pedestal of the Jina Tirthankara sculpture - Temples of India Project Team (Jio Institute, 2024)
The pedestal of the Jina Tirthankara sculpture which is found in the ruined shrines to the west of the main Jain Temple has 16th-century inscriptions. A cursory glance at the orthography and script of the inscriptions indicates that they belong to the 16th century, probably recording the consecration of the sculpture. The inscription is divided into four parts, on four portions of the pedestal.